2018
DOI: 10.1007/s12039-018-1551-z
|View full text |Cite
|
Sign up to set email alerts
|

Base-free oxidation of 5-hydroxymethyl-2-furfural to 2,5-furan dicarboxylic acid over basic metal oxide-supported ruthenium catalysts under aqueous conditions

Abstract: Polyethylene terephthalate (PET) is the third-largest globally produced polymer, and many efforts have been made to replace PET with a renewable polymer. One renewable alternative to PET is polyethylene furanoate (PEF), which is prepared using 2,5-furan dicarboxylic acid (FDCA) as a precursor instead of terephthalic acid (TPA). Biomass-derived hydroxymethyl-2-furfural (HMF) can be converted to 2,5-furan dicarboxylic acid (FDCA) through multiple oxidation reactions. Metal oxide-supported Ru catalyst prepared by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…For similar metal loadings, lower times were required when basic supports were used instead of carbon supports (entries 17–18). MgAlO led to a quantitative yield, but the catalyst was not stable . The support partly dissolved in the strong acid media resulting from the oxidation.…”
Section: Clean Catalytic Oxidation Of Furansmentioning
confidence: 98%
See 2 more Smart Citations
“…For similar metal loadings, lower times were required when basic supports were used instead of carbon supports (entries 17–18). MgAlO led to a quantitative yield, but the catalyst was not stable . The support partly dissolved in the strong acid media resulting from the oxidation.…”
Section: Clean Catalytic Oxidation Of Furansmentioning
confidence: 98%
“…Supports with basic sites, hydroxyapatite (HAP), MgAlO, and MgO allowed 100% conversion and good yields. Gao et al attributed the almost stoichiometric yield to the availability of both acidic and basic sites around the highly dispersed RuNP on the surface of HAP support.…”
Section: Clean Catalytic Oxidation Of Furansmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to HT and LDH, some novel basic supports have been reported recently. Cho et al [101] investigated a series of basic metal oxide supported Ru catalysts and found the catalytic activity for HMF oxidation was related primarily to the basicity of support in the order of MgAlO > MgO > ZrO 2 > CeO 2 ) La 2 O 3 . Unexpectedly, the most active MgAlO support was not stable under the catalytic condition and seriously dissolved due to the poor resistance to the acidic nature of the produced FDCA.…”
Section: Other Basic Supports or Additivesmentioning
confidence: 99%
“…However, the stability of individual intermediates formed during the oxidation has received relatively little attention, and this limits the use of partial WAO in order to obtain fine chemicals. There is considerable data concerning acetic and formic acid, which are frequently formed in the process and have high resistance to oxidation; they are classified as major byproducts. Previous investigations have shown that DCAs can be attainable via different types of oxidative conversion of organic wastes and biomass. Moreover, there are reports on WAO processes where DCAs were obtained, but these were primarily focused only on short-chain DCA. Some researchers have demonstrated the complete removal of these short-chain DCAs under specific conditions, although the wider spectrum of their reactivity has not been studied. Accordingly, there is still a deficiency of information on how environmentally friendly routes such as WAO can be used for the production of DCAs, especially for DCAs with longer aliphatic chains ( n > 4).…”
Section: Introductionmentioning
confidence: 99%